Evaluating the Role of Natural Resources, and Financial Development on Ecological Footprint in Pakistan: An ARDL Approach - Ahmad, Rana Israr; Ali, Sharafat; Khan, Hafiz M. Rizwan; Idrees, Sadia (iRASD Journal of Economics, 2024)
The role of economic growth, natural resources and financial development on ecological footprints in Pakistan. Data is applied between 1980 and 2021. Using ARDL bounds testing cointegration approach, the result signifies that the financial development, and natural resources have statistically significant with ecologic footprint. however, the economic growth has positive effect on ecologic footprint. Natural resources, economic expansion, and financial development were shown to be the driving forces behind the increase in ecological footprint because they all have a positive and significant influence on it. In long period, Pakistan data also supported the actuality of the Ecofriendly Kuznets Curve theory. Hence, the situation is advised to raise public mindfulness of the implementation of defensible applies in everyday lifespan and the routine of environmental technology that offer the greatest efficacy and the tiniest volume of environmental damage in business and household actions. Ultimately, based on the research findings, a thorough policy framework was suggested, which would enable the Pakistan economy to achieve the Sustainable Development Goals.